Eksistensi Tradisi Kaago-Ago pada Masyarakat Muna Kecamatan Batalaiworu Kabupaten Muna - Laras Mahardika; La Niampe; Rahmat Sewa Suraya (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2022)
The Kaago-ago tradition is a tradition carried out before the change of seasons which is held twice a year and plays a role in preventing disease. The purpose of this study was to describe its existence and analyze the development of the Kaago-ago Tradition in Wakorambu Village, Batalaiworu District, Muna Regency. The results of this study indicate that the background of the Kaago-ago tradition in the Muna community is a spirit who lives in two places, namely in the west and east. According to the local people's belief that every time there will be a change in the west season or east season, all kinds of diseases caused by the actions of spirits appear so that the Kaago-ago tradition is carried out as a ritual to prevent disease from entering the community. The development of the Kaago-ago tradition can be seen from the place where it was implemented, which used to be in the middle of Wakorambu village, but now it is held in the mosque. The effort to maintain the Kaago-ago tradition is by routinely carrying out the Kaago-ago tradition every year, involving the entire local community and studying the Kaago-ago tradition so as not to forget it.